Seleção e avaliação de prestadores de serviços de terceirização da tecnologia da informação nas empresas do setor farmacêutico - Ferreira, José Anibal (2008)
This dissertation, carries out an exploratory research, in the scope of the companies of the sector druggist, in the adhesion of the outsourcing of information technology (IT), in that to be identified the procedures of evaluation and criteria of selection utilized for the choice of supplying companies of this kind of service. To empirical research contemplates two multinational and two national companies. Approach the information technology and evolution of the IT services outsourcing in the industry druggist. The methodology of research utilized was the multiple case study, what permitted to the researcher the deepening in aspects of the trial of selection and criteria of choice adopted companies for contracting services providers. To research was carried out on the basis of interviews with executives or managers of IT that act in the trial of selection in four companies that already possess IT outsourcing service contracts. The interviews were driven according to script, from the model of research. The end of the work, present results of the research applied in the four druggist companies to the procedures of evaluation and the synthesis of the service suppliers choice criteria of IT. The results reveal the immaturity of the companies interviewed in the contracting IT services. The majority of the companies researched considers, of general form, a rank of importance elevated for the procedures of evaluation and criterion of choice, but of practical interest do not do, or better, do not possess tools perform-them, what is going to conclude that exists an amateurism in the choice of the suppliers of IT services, what provides risks for the company. The application of the model proposed in this work will be able to help the companies it minimize risks in the outsourcing service acquisition of IT